GLOBAL RESEARCH TRENDS ON MISCONCEPTIONS IN MOTION: BIBLIOMETRIC LITERATURE REVIEW - Lalu Ahmad Didik Meiliyadi; Isniwana Damayanti; Kurniawan Arizona; Muh. Wahyudi (Relativitas: Jurnal Riset Inovasi Pembelajaran Fisika, 2026)
Misconception is a condition where students' concept understanding is different from the opinion of experts. Many misconceptions occur in physics learning, one of which is motion material. The purpose of this study is to mapping research on misconceptions on the concept of motion so that it can be a further reference for research on misconceptions in motion materials. The database was obtained through the Scopus web for 20 periods (2005 to 2024). The data search resulted in 353 relevant research articles. The results of data analysis show that the development of research on misconceptions in motion material shows an increase in the number of publications. The most popular development of research on misconceptions in motion material occurred in 2020. The country that produces the most articles about research on misconceptions in motion material comes from the United States. Most of the published articles are in journals indexed in the Scopus database. The author affiliation with the most publications came from Padang State University. This study successfully used bibliometric analysis to describe the development of research on misconceptions in motion materials.